Euthanasia services - Ladki, Said M. (2016)
This paper explores euthanasia as a medical tourism product. Euthanasia and physician assisted suicide are generating much controversy and have been legalized in some countries and banned in others. The study examines the trends, characteristics and legality of euthanasia as tourism product. A comparative analysis between selected western (Netherlands, Mexico) and eastern countries (Japan, India) is provided. Euthanasia services are gaining popularity and becoming tourism pull factors in few western countries. Whereas, eastern countries provide euthanasia services only to the local population. The research showed that countries with strong religious convictions tend to oppose euthanasia more than those with less religious convictions. Due to “Die with Dignity” campaign, the number of euthanasia supporters in developed countries is increasing tremendously. An increasing number of affluent residents of the world will continue to travel to euthanasia service providing western countries in the pursuit of a new tourism product (euthanasia).